2018
DOI: 10.3390/nano8050291
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of New Materials Based on Lavender and Basil Essential Oils and Hydroxyapatite

Abstract: This study presents, for the first-time, the results of a study on the hydrodynamic diameter of essential oils (EOs) of basil and lavender in water, and solutions of EOs of basil (B) and lavender (L) and hydroxyapatite (HAp). The possible influence of basil and lavender EOs on the size of hydroxyapatite nanoparticles was analyzed by Scanning Electron Microscopy (SEM). We also investigated the in vitro antimicrobial activity of plant EOs and plant EOs hydroxyapatite respectively, against Gram-positive bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 79 publications
7
77
0
1
Order By: Relevance
“…The results highlighted that the use of DMSO as solvent did not affect bacterial growth. The results regarding the antimicrobial activity of HAp solution and DMSO are in agreement with previously reported studies by the authors [20,25]. Even though, the pharmacologic effects of DMSO are diverse and it has been reported to present anti-inflammatory, cryopreservative, antiischemic, radioprotective qualities and even antiseptic properties [37] its effect on microorganisms depends on numerous factors such as microbial strain, concentration, pH, etc [38].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results highlighted that the use of DMSO as solvent did not affect bacterial growth. The results regarding the antimicrobial activity of HAp solution and DMSO are in agreement with previously reported studies by the authors [20,25]. Even though, the pharmacologic effects of DMSO are diverse and it has been reported to present anti-inflammatory, cryopreservative, antiischemic, radioprotective qualities and even antiseptic properties [37] its effect on microorganisms depends on numerous factors such as microbial strain, concentration, pH, etc [38].…”
Section: Resultssupporting
confidence: 89%
“…The measurements were conducted as previously described in Predoi et al [35]. Additionally, a Perkin-Elmer Turbomass Quadrupole mass spectrometer (PerkinElmer Inc., Waltham, MA, USA) was used for the GC/MS studies [20]. The chemical elements of the studies sample were identified using NIST and Wiley Registry 8 Edition mass database, n-alkalene (C 9 -C 22 ) hydrocarbon series (Nile, Italy).…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These days, one of the most distressing complications that could appear after surgery is considered the apparition of a post operatory infection [5,6]. In most cases, the infection appears because of the bacterial cells, which adhere either to an implantable medical device (when is the case), either on the tissue surrounding the surface of the implant, or simply on the surface of the wound [7,8]. These types of bacterial adhesions on implantable devices are some of the most frightening problems that can occur in the dentistry, orthopedic, and cardiovascular field, because they usually lead to severe life treating infections due to the development The morphology of the samples was investigated by scanning electron microscopy (SEM), using a HITACHI S4500 microscope (Hitachi, Ltd., Tokyo, Japan) equipped with an X-ray energy dispersive spectroscopy (EDX) system.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained considering some agglomeration of the particles; indeed such agglomeration and the difference between SEM and DLS results was previously observed for HAp‐based nanomaterial. The agglomeration can be due to the OH groups present in the HAp molecule and the hydrogen bond‐type interactions; the presence of iron ion in the powders also seem to favor the agglomeration …”
Section: Resultsmentioning
confidence: 99%